O sistema das artes em Belo Horizonte - Laura Dolabella Barbi (2022)
This thesis researches the visual arts system in Belo Horizonte. In particular, the relationship between the artist, active today, the arts system and the public. The brazilian art system, despite being included in a global scenario, is considered incipient and has different realities between the Rio-São Paulo axis and the other regions and capitals of Brazil. This thesis intends to demonstrate how relationships between their agents in these peripheral axes are configured, especially in Belo Horizonte. The challenges faced by artists working in the capital of Minas Gerais in relation to their production process, dissemination of their work and (self) insertion in the market. The impact of contemporary art galleries, independent initiatives, museums and institutional spaces, artistic residencies, critics, curators and cultural producers and the internet on the system's expansion path. The norms for validating the art created today, which are established by the international arts market as a means of consolidating, evaluating the artistic process and the consequent legitimation of the artist and the work of art. Its expanded relevance in a local context at a time in which the lack of Governmental budgets and cultural incentives are being discussed, as well as the need to decentralize and diversify the artistic production of visual arts is discussed, and the expansion of their access to the arts market.